A surge of Indigenous graphic novels - Rheault, Sylvain (Journal of graphic novels & comics, 2020)
This article surveys Indigenous graphic novels created between the year 2000 and 2017 and identifies some trends in the corpus. Because information is still scarce on this subject, three Indigenous creators were interviewed for this article: Jason EagleSpeaker, David Alexander Robertson and Sean Muir. After discussing the inadequacy of the term 'Canadian' to qualify the nationality of Indigenous creators, a chronological inventory of Indigenous graphic novels reveals that only two were published before the year 2000 and that the production really started in 2008. Indigenous publishers are also surveyed. Among the most important trends in the corpus, there seems to be an overarching purpose of education in Indigenous graphic novels. There is also a desire to rewrite history with an Indigenous perspective, as well as a strong wish to show that Indigenous culture is alive today and not a remnant of the past. Indigenous creators are also using the medium of the graphic novel to express their Indigenous identity while making their voice heard to a public as wide as possible.